2020
DOI: 10.3390/pr8111434
|View full text |Cite
|
Sign up to set email alerts
|

Structure Property Investigation of Glass-Carbon Prepreg Waste-Polymer Hybrid Composites Degradation in Water Condition

Abstract: The limited shelf life of carbon prepreg waste (CPW) from component manufacturing restricts its use as a composite reinforcement fibre on its own. However, CPW can be recycled with glass fibre (GF) reinforcement to develop a unique remediate material. Therefore, this study fabricated (1) a glass fibre-carbon prepreg waste reinforced polymer hybrid composite (GF-CPW-PP), (2) a polypropylene composite (PP), (3) a carbon prepreg waste reinforced composite (CPW-PP), and (4) a glass fibre reinforced composite (GF-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…With the advance of TPCs as a result of the increasing use of high performance fibers, the need for the detailed characterization of these novel material combinations is emerging. Although several studies have been performed to assess the mechanical properties of hybrid TPCs as reported by Asenjan et al, 12 Barczewski et al, 35 Zulkafli et al, 36 and Nosbi et al, 37 research studies on the effect of AFs and CFs hybridization on the glass fiber-reinforced PP and its quasi-static perforation behavior can be hardly found. Furthermore, composites can be used at various temperatures that may cause degradation in matrix material and fiber/matrix interface.…”
Section: Introductionmentioning
confidence: 99%
“…With the advance of TPCs as a result of the increasing use of high performance fibers, the need for the detailed characterization of these novel material combinations is emerging. Although several studies have been performed to assess the mechanical properties of hybrid TPCs as reported by Asenjan et al, 12 Barczewski et al, 35 Zulkafli et al, 36 and Nosbi et al, 37 research studies on the effect of AFs and CFs hybridization on the glass fiber-reinforced PP and its quasi-static perforation behavior can be hardly found. Furthermore, composites can be used at various temperatures that may cause degradation in matrix material and fiber/matrix interface.…”
Section: Introductionmentioning
confidence: 99%